2012
DOI: 10.4103/0975-7406.100251
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and periodontal disease

Abstract: Diabetes mellitus is a systemic disease characterized by increased blood glucose levels and abnormalities of lipid metabolism due to absence or decreased level of insulin. It affects all the body organs and their functions either directly or indirectly. Every dentist should have a basic understanding of the etiopathogenesis, oral and systemic manifestations of this disease. The periodontal diseases are a consequence of extension of the gingival inflammation into the underlying supporting structures of the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 10 publications
0
35
0
1
Order By: Relevance
“…There is a two‐way relationship between these two diseases, so that diabetes mellitus may increase the risk of periodontal disease, and vice versa (Grover and Luthra, ). It was reported that the prevalence of severe periodontitis is approximately 39 to 59.6% higher in patients with diabetes than in patients without diabetes (Daniel et al , ). The risk of periodontal disease is three times greater in subjects with diabetes than in subjects without diabetes (Stanko and Izakovicova Holla, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a two‐way relationship between these two diseases, so that diabetes mellitus may increase the risk of periodontal disease, and vice versa (Grover and Luthra, ). It was reported that the prevalence of severe periodontitis is approximately 39 to 59.6% higher in patients with diabetes than in patients without diabetes (Daniel et al , ). The risk of periodontal disease is three times greater in subjects with diabetes than in subjects without diabetes (Stanko and Izakovicova Holla, ).…”
Section: Introductionmentioning
confidence: 99%
“…Another correlation between periodontitis and diabetes also has been well documented. Higher plaque levels and higher incidence of chronic gingivitis are both found in adults and in children with diabetes [43,44]. Periodontal treatment showed a beneicial efect on metabolic control of type 2 diabetic patients.…”
Section: Periodontitismentioning
confidence: 94%
“…The alteration of collagen metabolism by the glycosylation of the collagen molecules and vascular basement membrane thickening due to defective cross linking of collagen fibres causes narrowing of capillaries and henceforth delayed healing [12]. These cascades of events occur in periodontium of diabetic subjects leading to the alteration of host defensive cycle.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Although there are several risk factors for periodontitis, diabetes mellitus has been until now , the only systemic disease connected through biochemical mechanism with periodontal disease(Gheric et al 2008) [14] . Another fact related to the relationship between periodontitis and diabetes is majority of well controlled studies show a higher prevalence and severity of periodontal disease in diabetes than in non-diabetes with similar local irritation including greater loss of attachment, alveolar bone loss, bleeding gums on probing and tooth mobility [12].…”
Section: Association Between Periodontitis and Diabetesmentioning
confidence: 99%